A Clinical Study on Management of Incomplete Abortion by Manual Vacuum Aspiration (MVA) (Journal of Enam Medical College, 2012)
Background: Abortion is an important social and public health issue. In Bangladesh   complication from unsafe abortion is one of the leading causes of maternal mortality. It is a  serious health problem. World Health Organisation estimates that 14% of maternal deaths which occur every year in the countries of South Asia including Bangladesh are due to        abortion. Study shows manual vacuum aspiration procedure is safe and effective in incomplete abortion. Very few clinical trials were carried out in Bangladesh to assess the safety and effectivity of manual vacuum aspiration in managing incomplete abortion.Objective: To find out the outcome of manual vacuum aspiration in the management of patients of incomplete abortion.Materials and Methods: This observational descriptive study was conducted in the department of Obstetrics & Gynaecology, Dhaka Medical College & Hospital from June to December, 2004. One hundred cases of diagnosed incomplete abortion up to 12 weeks of gestation were managed by manual vacuum aspiration during this period. A data recording sheet was designed for this purpose. Haemodynamically stable patients with no history of induced abortion and fever were enrolled. Results: Procedure time of manual vacuum aspiration was short, average duration was 7 minutes. Bleeding was minimum (20-30 mL) in 67% cases and weighted mean was 29.80 mL. Eighty three percent patients were stable during the procedure and only 3% needed blood transfusion. Nonnarcotic analgesics were used in 59% cases and 33% needed only proper counselling. Average duration of hospital stay was 2 hours. Effectiveness of the procedure was about 98% with very low post procedure complication rate (2%). Conclusion: MVA procedure is a safe and effective technique of uterine evacuation in incomplete abortion. It is quick, less expensive, effective and less painful. Hospital stay and chance of perforation of uterus is less. So this procedure should be considered by health care system in Bangladesh for improving treatment of incomplete abortion to reduce both maternal morbidity and mortality. DOI: http://dx.doi.org/10.3329/jemc.v2i1.11918 J Enam Med Col 2012; 2(1): 24-28